Finite element stress analysis study for stresses around mandibular implant retained overdenture MIR-OD - Jassim, Raghdaa K; Ibrahim, Ibrahim K (Journal of Baghdad College of Dentistry, 2014)
Background: It has been well known that the success of mandibular implant- retained overdenture heavily depends on initial stability, retention and long term osseointegration this is might be due to optimal stresses distribution in surrounding bones. Types of mandibular implant- retained overdenture anchorage system and number of dental implants play an important role in stresses distribution at the implant-bone interface. It is necessary to keep the stresses below the physiologic tolerance level of the bone .since. And it is difficult to measure these stresses around bone in vivo. In the present study, finite element analysis used to study the stresses distribution around dental implant supporting Mandible implant retained overdentureMaterials and methods: Eight models were constructed including four designs of anchorage system (ball-cup, ball-O Ring, bar without distal extension and bar with distal extension).The first group of models were supported by four dental implant and second group of models were supported by two dental implant only. Models constructed from the data obtained directly from patient The contour of bone was obtained from C.T scan image of patient, then data transferred to ANSYS program for modeling then load applied and solve the equation by the program, Specified nodes were selected at the rings of crestal bone (cortical bone) and cortical cancellous interface around each dental implant and fixed for all models to monitor the stress change in that regions of different design of MIR-OD.. After load application, Specified nodes were selected at the rings of crestal bone (cortical bone) and cortical cancellous interface around each dental implant and fixed for all models to monitor the stress change in that regions of different design of MIR-OD . Results: In the present study the stress distribution and maximum stresses value around dental implant had a relationship to the number of dental implant. , The result appeared that the maximum stresses and means of stresses value was lower in the first group of models (which was supported through the use four dental implant) than the second group of models (which was supported through the use of two dental implant only). For the first group of models the maximum stresses value around mesial implant was11.67, 10.51, 10.98 and 10.72 Mpa, while the maximum stresses around distal implant was 21.33, 18.51, 18.86, and17.56 Mpa for models 1,2,3 and 4respectively ,and the stresses around implant supporting second group of models was 22.52, 22.16, 20.51 and 19.60 Mpa for models 5,6,7and8 respectively .Statistical analyses of means value appeared that there was statistically significant difference in stresses means value around implant of the second group with that’s values around mesial and distal implant supporting first group of model . Regarding the result of both ball and bar system, it has been demonstrated that stress was greater with ball attachment and MIR-OD supported by the use of four dental implants and anchored by bar attachments with distal extension gives the minimum values of stresses than the rest models. Also the results show that higher stresses value was appeared at the cortical bone ring surrounding dental implant especially the distal implant nearest to the free end extension area. Also it was appeared that the best model was Mandible implant- retained overdenture that’s anchored by bar with distal extension and support by four dental implant. Conclusions: Bar-clips with distal extension mode of attachment considered the best type in producing the least stresses around dental implant regardless number of dental implant used.